A core-shell structured carbon-supported PtSn4 / Pt nanoparticle catalyst, its preparation method and application
By growing island-like Pt structures on the surface of PtSn4 nanoparticles and loading carbon-backed PtSn4/Pt nanoparticles catalysts on carbon black, the problem of poisoning and inactivation of Pt-based catalysts during ethanol oxidation is solved, and excellent electrocatalytic ethanol oxidation activity and anti-CO poisoning performance are achieved.
Patent Information
- Application Number
- CN202211356592.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-01
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2042-11-01
AI Technical Summary
Existing Pt-based catalysts are prone to poisoning and inactivation during ethanol oxidation, which limits their commercial development.
A core-shell-like structure carbon-supported PtSn4/Pt nanoparticle catalyst was used to grow island-like Pt structures on the surface of PtSn4 nanoparticles by a two-step growth method, and load them on carbon black to form a catalyst with excellent electrocatalytic properties and anti-CO poisoning properties.
The electrocatalytic oxidation activity and anti-CO poisoning properties of ethanol were improved, with the oxidation potential of ethanol at 0.613V vs. SCE and the mass activity was 0.567A mg-1Pt, which was better than commercial PtC.
Smart Images

Figure CN115663219B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a core-shell structured carbon-supported PtSn4 / Pt nanoparticle catalyst and a preparation method and application thereof, and belongs to the field of catalyst preparation and electrochemical energy. Background Art
[0002] The use of traditional energy causes great damage to the environment. In addition, there are problems such as low conversion efficiency in the process of converting fossil energy into electrical energy. In order to solve this problem, fuel cell power generation technology has been widely studied.
[0003] The most popular research at present is the proton membrane fuel cell, which is divided into hydrogen-oxygen fuel cells and alcohol fuel cells according to the different anode fuels. Hydrogen-oxygen fuel cells use hydrogen as the battery anode fuel, while alcohol fuel cells use organic small molecule alcohols as the anode fuel, which can be divided into direct methanol fuel cells and direct ethanol fuel cells. Compared with hydrogen, alcohol fuels have a wide range of raw material sources, high energy density, and are easy to store. However, due to the shortcomings of methanol, such as low boiling point, high volatility, harmful to the human body, and easy penetration of Nafion membranes, the commercial application of direct methanol fuel cells is limited. Ethanol has a similar structure to methanol, is non-toxic, renewable, and safe to use, and is a renewable and environmentally friendly energy source.
[0004] At present, Pt-based catalysts are still the main anode catalysts for direct ethanol fuel cells. However, Pt is a precious metal element with low content in the earth's crust. In addition, ethanol is prone to produce strongly adsorbed intermediates such as CO during the oxidation process to CO2. ads etc., are strongly adsorbed on the Pt surface, causing catalyst poisoning and deactivation, which seriously limits the commercial development of Pt-based catalysts.
[0005] To solve this problem, researchers usually alloy Pt with other metals or prepare a Pt-based core-shell structure. Due to the geometric effect between different metals, it can not only improve the ethanol electrocatalytic activity but also reduce the Pt content in the catalyst.
[0006] For example, Chinese patent document CN114784296A discloses a method for preparing a catalyst for the oxidation of methanol and ethanol using a ternary alloy nanomaterial doped with a rare earth element.
[0007] For example, Chinese patent document CN106299396B discloses a method for preparing a PtSn-ZrO2 / GN ethanol fuel cell anode catalyst, which uses graphene (GN) as a carrier and ZrO2 as an active component doped in a PtSn alloy material.
[0008] As a co-catalyst in ethanol oxidation, most of the current reports are about the application of Pt and Sn alloy materials as catalysts. The Pt and Sn alloy catalytic materials have a small specific surface area and low catalytic performance. Summary of the invention
[0009] In view of the deficiencies in the prior art, the present invention provides a core-shell structured carbon-supported PtSn4 / Pt nanoparticle catalyst and a preparation method and application thereof. Summary of the invention:
[0011] The present invention uses PtSn4 intermetallic compound nanoparticles as cores, adopts a two-step growth method to reduce and grow a Pt metal salt solution on PtSn4 nanoparticles, and grows Pt in an island structure on the surface of the PtSn4 nanoparticles serving as the core, thereby obtaining a PtSn4 / Pt nanomaterial with a core-shell structure. Finally, the material is loaded on carbon black to obtain a core-shell carbon-supported PtSn4 / Pt nanoparticle, which has excellent electrocatalytic ethanol oxidation performance and excellent CO poisoning resistance.
[0012] The nanomaterial combining the intermetallic compound with the Pt shell can improve the ethanol oxidation catalytic performance by combining the synergistic effect between different metals, while reducing the Pt content. Detailed description of the invention:
[0014] The present invention is achieved through the following technical solutions:
[0015] A core-shell structured carbon-supported PtSn4 / Pt nanoparticle catalyst, wherein Pt grows in an island structure on the surface of PtSn4 nanoparticles serving as cores, the surfaces of the PtSn4 nanoparticles are wrapped by island-like Pt particles to form PtSn4 / Pt core-shell structured nanoparticles with rough surfaces, and the PtSn4 / Pt core-shell structured nanoparticles are supported on carbon black.
[0016] The preparation method of the above-mentioned core-shell structure carbon-supported PtSn4 / Pt nanoparticle catalyst comprises the following steps:
[0017] (1) Preparation of PtSn4 nanoparticles: Platinum acetylacetonate (Pt(acac)2) and anhydrous stannous chloride (SnCl2) were mixed with tungsten carbonyl (W(CO)6) as metal salt precursors, and hexamethyldisilazane (HMDS), oleylamine (OAm) and 1-octadecene (ODE) were added, stirred evenly under an argon atmosphere, heated to react, and naturally cooled to room temperature after the reaction was completed. The mixture was centrifuged and washed to obtain PtSn4 nanoparticles;
[0018] (2) Preparation of PtSn4 / Pt nanoparticles: dissolving platinum acetylacetonate (Pt(acac)2) in oleylamine (OAm) to obtain a Pt precursor solution (Pt-OAm); mixing PtSn4 nanoparticles, oleylamine (OAm) and 1-octadecene (ODE) and dispersing them by ultrasonication, heating the mixture under an Ar atmosphere, and slowly dropping the Pt precursor solution into the system with a syringe. After the dropping is completed, the reaction is continued. After the reaction is completed, the system is naturally cooled to room temperature, centrifuged, and washed to obtain PtSn4 / Pt nanoparticles with a core-shell structure.
[0019] (3) Taking carbon black XC-72 and dispersing it uniformly in n-hexane solution by ultrasonication to obtain carbon black dispersion, dispersing PtSn4 / Pt nanoparticles in n-hexane to obtain PtSn4 / Pt nanoparticle dispersion, adding the PtSn4 / Pt nanoparticle dispersion into the carbon black dispersion, and continuing ultrasonication to completely load the nanoparticles on the carbon black; collecting the solid by centrifugation to remove the organic ligands on the surface of the sample, centrifuging, and drying to obtain a core-shell structured carbon-supported PtSn4 / Pt nanoparticle catalyst.
[0020] Preferably according to the present invention, in step (1), the mass ratio of acetylacetonate platinum (Pt(acac)2) to anhydrous stannous chloride (SnCl2) is 1:(1-3).
[0021] Preferably according to the present invention, in step (1), the mass ratio of platinum acetylacetonate (Pt(acac)2) to W(CO)6 is 1:(1-3).
[0022] Preferably according to the present invention, in step (1), the volume ratio of hexamethyldisilazane (HMDS), oleylamine (OAm) and 1-octadecene (ODE) is 1:(3-8):(3-8).
[0023] Preferably according to the present invention, in step (1), the mass volume ratio of acetylacetonate platinum (Pt(acac)2) to hexamethyldisilazane (HMDS) is (10-30):1, unit, mg / ml.
[0024] According to the preferred embodiment of the present invention, in step (1), the heating rate is 5-15°C / min.
[0025] Preferably according to the present invention, in step (2), the concentration of Pt in the Pt precursor solution (Pt-OAm) is 0.005-0.02 mmol / ml.
[0026] Preferably, according to the present invention, in step (2), the droplet acceleration rate of the Pt precursor solution is 0.1-0.3 ml / min.
[0027] Preferably according to the present invention, in step (2), the volume ratio of OAm and ODE solution is 1:(1-3), the volume ratio of the molar amount of PtSn4 nanoparticles to oleylamine is (0.02-0.06):(2-8), unit, mol / L, and the volume ratio of Pt precursor solution (Pt-OAm) to oleylamine is (1-4):1.
[0028] According to the preferred embodiment of the present invention, in step (2), the temperature is raised in an Ar atmosphere at 8-12°C min -1 The heating rate is increased to 170-200°C and maintained for 4-8 minutes.
[0029] Preferably according to the present invention, in step (3), the concentration of carbon black in the carbon black dispersion is 3-10 mg / ml.
[0030] Preferably according to the present invention, in step (3), PtSn4 / Pt nanoparticles are dispersed in n-hexane, and the concentration after dispersion is 0.005-0.02 mmol / ml.
[0031] Preferably according to the present invention, in step (3), the volume ratio of the carbon black dispersion to the PtSn4 / Pt nanoparticle dispersion is (1-2): (1-2).
[0032] The present invention also provides the use of the above-mentioned core-shell structure carbon-supported PtSn4 / Pt nanoparticle catalyst as a catalyst for electrocatalytic ethanol oxidation.
[0033] The specific application methods are as follows:
[0034] At room temperature, 2 mg of catalyst sample was dispersed in a mixed solution of 300 ul deionized water and 300 ul isopropanol, 100 ul of Nafion solution with a mass concentration of 0.5‰ was added, and the mixture was mixed by ultrasonic for 30 minutes to obtain a catalyst slurry. Then 10 ul of the slurry was dropped onto the surface of a glassy carbon electrode with a diameter of 5 mm. After the slurry was dry, it was used as a working electrode.
[0035] The beneficial effects of the present invention are as follows:
[0036] 1. The core-shell structure carbon-supported PtSn4 / Pt nanoparticle catalyst of the present invention, the surface of the PtSn4 nanoparticle is wrapped by island-shaped Pt particles to form PtSn4 / Pt core-shell structure nanoparticles with rough surface, the PtSn4 / Pt core-shell structure nanoparticles are supported on carbon black, have a larger specific surface area, provide more ethanol oxidation active sites, thereby improving the ethanol electrocatalytic oxidation activity, and show excellent electrochemical activity under acidic conditions.
[0037] 2. The core-shell carbon-supported PtSn4 / Pt nanoparticle catalyst of the present invention improves the electrocatalytic ethanol oxidation activity, with an ethanol oxidation potential of 0.613 V vs. SCE and a mass activity of 0.567 A mg better than that of commercial PtC. -1 Pt . BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The X-ray diffraction pattern of PtSn4 / Pt 1:1 prepared in Example 2.
[0039] Figure 2 Transmission electron microscopy image of PtSn4 / Pt 1:1 prepared in Example 2.
[0040] Figure 3 Element distribution map of PtSn4 / Pt 1:1 prepared for Example 2.
[0041] Figure 4 The cyclic voltammetry curves of electrochemical ethanol oxidation of Example 4, Comparative Example 1 and commercial Pt / C are shown.
[0042] Figure 5 The electrochemical ethanol oxidation cyclic voltammetry curves of Example 4 and Example 5 are shown.
[0043] Figure 6 It is a comparison chart of CO adsorption and desorption curves of Example 4, Comparative Example 1 and commercial Pt / C. DETAILED DESCRIPTION
[0044] The present invention is further described below in conjunction with specific embodiments.
[0045] In the following examples, the main experimental reagents used are listed below:
[0046] Platinum acetylacetonate (Pt(acac)2), stannous chloride (SnCl2), tungsten carbonyl (W(CO)6), oleylamine (OAm, 80-90%), 1-octadecene (ODE, >90%), hexamethyldisilazane (C6H 19 NSi2), n-hexane (C6H 14 ), anhydrous ethanol (C2H6O), acetone (C3H6O), glacial acetic acid (C2H4O2), carbon black (XC-72), sulfuric acid (H2SO4), Nafion (5wt%), isopropyl alcohol (C3H6OH);
[0047] Commercial Pt / C, commercially available product.
[0048] Example 1 Preparation of PtSn4 Nanoparticles
[0049] Weigh 20 mg (0.05 mmol) of platinum acetylacetonate, 40 mg of stannous chloride and 50 mg of tungsten hexacarbonyl into a 50 mL three-necked flask, add 4.5 mL of 1-octadecene, 4.5 mL of oleylamine, and 1 ml of hexamethyldisilazane (HMDS). Put in a magnetic bar, turn on the magnetic stirrer, and mix the reactants evenly under the condition of passing saturated argon gas into the reaction system. Then, under magnetic bar stirring and argon protection, heat at 10 ° C min -1 The temperature was raised to 240 °C at a heating rate and maintained at 240 °C for 1 h. After the reaction was completed, it was naturally cooled to room temperature. The liquid in the three-necked flask was then transferred to a centrifuge tube with a dropper, 5 mL of n-hexane and 15 mL of ethanol were added for washing, and the tube was centrifuged at 9000 rpm for 5 min to obtain PtSn4 nanoparticles.
[0050] Example 2 Preparation of PtSn4 / Pt 1:1 Nanoparticles
[0051] Platinum acetylacetonate was dissolved in oleylamine to prepare a Pt precursor solution. The concentration of Pt in the Pt precursor solution (Pt-OAm) was 0.01 mmol / ml. 0.025 mmol PtSn4 nanoparticles were dispersed in a mixed solution of 5 ml 1-octadecene and 2.5 ml oleylamine. The solution was placed in a round-bottom three-necked flask, a magnet was placed in it, and a magnetic stirrer was turned on. The reaction system was placed under argon and the appropriate speed was adjusted to mix the reactants evenly. Then, the mixture was stirred at 10 °C min -1 The heating rate was raised to 180°C and maintained for 5 min. After the temperature stabilized, 2.5 ml of Pt precursor solution was slowly added at a rate of 0.2 ml / min. After the addition was completed, the temperature was maintained at 180°C for 1 h. After the reaction was completed, it was naturally cooled to room temperature and centrifuged at 9000 rpm for 5 min to obtain PtSn4 / Pt 1:1 nanoparticles.
[0052] Example 3 Preparation of PtSn4 / Pt 1:2 Nanoparticles
[0053] The preparation of nanoparticles is the same as that described in Example 2, except that the amount of Pt precursor solution added is 5 ml. The rest is carried out as in Example 2 to obtain PtSn4 / Pt 1:2 nanoparticles.
[0054] Example 4 Preparation of Carbon-supported PtSn4 / Pt 1:1 Nanoparticles (PtSn4 / Pt / C 1:1)
[0055] Weigh 40 mg of carbon black (XC-72) and place it in 10 ml of n-hexane solution for 1 hour to make it dispersed evenly. Then disperse the PtSn4 / Pt 1:1 prepared in Example 2 in 5 ml of n-hexane to obtain a PtSn4 / Pt nanoparticle dispersion. The concentration of PtSn4 / Pt 1:1 in n-hexane is 0.01 mmol / ml. Add the PtSn4 / Pt nanoparticle dispersion to the carbon black dispersion and continue to ultrasonicate for 1 hour to completely load the nanoparticles on the carbon black; centrifuge at 9000 rpm for 5 minutes, then re-disperse with a mixed solution of glacial acetic acid / acetone in a ratio of 1:3, and ultrasonicate for 1 hour to remove the organic ligands on the surface of the nanoparticles. Centrifuge at 9000 rpm for 5 minutes, then place the precipitate in a vacuum drying oven at 60°C and dry for 12 hours to obtain a core-shell carbon-supported PtSn4 / Pt nanoparticle catalyst.
[0056] Example 5 Preparation of Carbon-supported PtSn4 / Pt 1:2 Nanoparticles (PtSn4 / Pt / C 1:1)
[0057] The preparation of nanoparticles is the same as that described in Example 4, except that the PtSn4 / Pt 1:2 prepared in Example 3 is dispersed in 5 ml of n-hexane, and the rest is carried out as in Example 4 to obtain carbon-supported PtSn4 / Pt 1:2 nanoparticles (PtSn4 / Pt / C1:1).
[0058] Comparative Example 1 Preparation of carbon-supported PtSn4 nanoparticles (PtSn4 / C)
[0059] Weigh 40 mg of carbon black (XC-72) and place it in 10 ml of n-hexane solution for 1 hour to make it dispersed evenly. Then disperse the PtSn4 prepared in Example 1 above in 5 ml of n-hexane and mix it with the carbon black dispersion. Ultrasonicate for 1 hour to make PtSn4 completely loaded on the carbon black. Centrifuge at 9000 rpm for 5 minutes, then re-disperse with a mixed solution of glacial acetic acid / acetone with a ratio of 1:3, and ultrasonicate for 1 hour to remove the organic ligands on the surface of the nanoparticles. Centrifuge at 9000 rpm for 5 minutes, and then place the precipitate in a vacuum drying oven at 60°C and dry for 12 hours.
[0060] Test Example 1
[0061] The PtSn4 / Pt 1:1 nanoparticles obtained in Example 2 were characterized and tested as follows:
[0062] X-ray Diffraction (XRD): Figure 1The X-ray diffraction pattern of PtSn4 / Pt 1:1 prepared in Example 2. It can be seen that the X-ray diffraction (XRD) diffraction patterns of PtSn4 / Pt 1:1 nanoparticles correspond to PtSn4 (JCPDF: 04-0744) and Pt (JCPDF: 04-0802), respectively. The present invention successfully synthesized PtSn4 / Pt nanoparticles.
[0063] Transmission Electron Microscopy (TEM): Figure 2 This is a transmission electron micrograph of the PtSn4 / Pt 1:1 nanoparticles prepared in Example 2. It can be seen from the figure that the island structure grows on the surface of the PtSn4 nanoparticles as the core, forming a core-shell structure.
[0064] Energy Dispersive X-ray Spectroscopy - Element Distribution (EDS-Mapping): Figure 3 This is the distribution diagram of Pt and Sn elements in the PtSn4 / Pt 1:1 nanoparticles prepared in Example 2.
[0065] Test Example 2
[0066] The performance test of the carbon-supported PtSn4 / Pt 1:1 nanoparticles (PtSn4 / Pt / C 1:1) obtained in Example 4 is as follows:
[0067] 2mg carbon-supported PtSn4 / Pt 1:1 nanoparticle sample was dispersed into 300ul deionized water and 300ul isopropanol mixed solution, 100ul 0.05‰ Nafion solution was added and ultrasonically mixed for 30 minutes to obtain a uniform slurry, and then 10ul slurry was drop-coated on the surface of a 5mm diameter glassy carbon electrode as a working electrode. After the slurry was completely dry, the electrocatalytic ethanol oxidation test was performed. A three-electrode test system was used, saturated calomel (SCE) was used as the reference electrode, and a Pt sheet was used as the counter electrode. The test was performed on a Shanghai Chenhua chi1030c workstation.
[0068] Activity test: In an electrolyte containing 0.5 mol / L H2SO4 and 0.5 mol / L ethanol, the electrolyte was purged with argon for 30 minutes to remove oxygen in the solution, and a cyclic voltammetry curve was scanned in the potential range of -0.2 to 1 V vs. SCE at a scan rate of 20 mV / s, and compared with commercial Pt / C;
[0069] Anti-CO poisoning test: First, an it test was conducted in a CO-saturated 0.5 mol / L H2SO4 solution at a constant potential of -0.2 V vs. SCE for 1200 s; then, Ar was purged under the same test conditions, and finally, a cyclic voltammetry scan test was conducted in the potential range of -0.2 to 0.9 V vs. SCE at a scan rate of 20 mV / s, and compared with commercial Pt / C.
[0070] Figure 4 The cyclic voltammetry curves of electrocatalytic ethanol oxidation of Example 4, Comparative Example 1 and commercial Pt / C are compared. Figure 4 It can be seen that when the current density reaches 0.1A mg -1 Pt When the electrocatalytic ethanol oxidation potential of the PtSn4 / Pt / C of the present invention is 0.243V, while the ethanol oxidation potential of the PtSn4 / C of comparative example 1 is 0.303V, and the ethanol oxidation potential of the commercial Pt / C is 0.282V. The potential of the core-shell structured PtSn4 / Pt / C of the present invention is much lower than that of the comparative example 1 and the commercial Pt / C. In addition, the ethanol oxidation current density of the core-shell structured PtSn4 / Pt / C of the present invention can reach 0.567A mg -1 Pt , much higher than 0.12A mg of PtSn4 / C -1 Pt The commercial Pt / C has a 0.33A mg -1 Pt It can be seen that the PtSn4 / Pt core-shell structure of the present invention has excellent electrocatalytic ethanol oxidation performance.
[0071] Figure 5 The figure is a comparison of the cyclic voltammetric curves of electrocatalytic ethanol oxidation of Example 4 and Example 5. Figure 5 It can be seen that the ethanol electrocatalytic oxidation performance of the PtSn4 / Pt / C 1:1 catalyst is better than that of the PtSn4 / Pt / C 1:2 catalyst.
[0072] Figure 6 The figure is a comparison chart of the anti-CO poisoning performance of Example 4, Comparative Example 1 and commercial Pt / C. Figure 6 It can be seen that the initial desorption potential of PtSn4 / Pt / C of the present invention for CO is 0.02V, which is significantly lower than PtSn4 / C (0.04V) and commercial Pt / C (0.456V). This shows that the PtSn4 / Pt core-shell structure nanomaterial prepared by the present invention has excellent anti-CO poisoning performance.
Claims
1. A core-shell structure carbon-supported PtSn4 / Pt nanoparticle catalyst, wherein Pt is grown in an island structure on the surface of a PtSn4 nanoparticle as a core, the surface of the PtSn4 nanoparticle is wrapped by the island-like Pt particles to form a rough surface PtSn4 / Pt core-shell structure nanoparticle, and the PtSn4 / Pt core-shell structure nanoparticle is supported on carbon black; It is prepared as follows: (1) Preparation of PtSn4 nanoparticles: Platinum acetylacetonate (Pt(acac)2) and anhydrous stannous chloride (SnCl2) were mixed with carbonyl tungsten (W(CO)6) as metal salt precursors, and hexamethyldisilazane (HMDS), oleylamine (OAm) and 1-octadecene (ODE) were added. The mixture was stirred evenly under an argon atmosphere and heated to react. After the reaction was completed, the mixture was naturally cooled to room temperature, centrifuged and washed to obtain PtSn4 nanoparticles. (2) Preparation of PtSn4 / Pt nanoparticles: dissolve platinum acetylacetonate (Pt(acac)2) in oleylamine (OAm) to obtain a Pt precursor solution (Pt-OAm); mix PtSn4 nanoparticles, oleylamine (OAm) and 1-octadecene (ODE) and disperse them by ultrasonication, heat the mixture under an Ar atmosphere, slowly drop the Pt precursor solution into the system with a syringe, continue the reaction after the dropwise addition is completed, and naturally cool the system to room temperature after the reaction is completed, centrifuge and wash to obtain PtSn4 / Pt nanoparticles with a core-shell structure; (3) Ultrasonic dispersion of carbon black XC-72 in n-hexane solution to obtain a carbon black dispersion, and PtSn4 / Pt nanoparticles are dispersed in n-hexane to obtain a PtSn4 / Pt nanoparticle dispersion. The PtSn4 / Pt nanoparticle dispersion is added to the carbon black dispersion, and ultrasonication is continued to completely load the nanoparticles on the carbon black; the solid is collected by centrifugation to remove organic ligands on the sample surface, and the sample is centrifuged and dried to obtain a core-shell structured carbon-supported PtSn4 / Pt nanoparticle catalyst.
2. The core-shell carbon-supported PtSn4 / Pt nanoparticle catalyst according to claim 1, characterized in that: In step (1), the mass ratio of platinum acetylacetonate (Pt(acac)2) to anhydrous stannous chloride (SnCl2) is 1:(1-3), and the mass ratio of platinum acetylacetonate (Pt(acac)2) to tungsten carbonyl (W(CO)6) is 1:(1-3).
3. The core-shell carbon-supported PtSn4 / Pt nanoparticle catalyst according to claim 1, characterized in that: In step (1), the volume ratio of hexamethyldisilazane (HMDS), oleylamine (OAm) and 1-octadecene (ODE) is 1:(3-8):(3-8), the mass volume ratio of acetylacetonate platinum (Pt(acac)2) and hexamethyldisilazane (HMDS) is (10-30):1, unit, mg / ml, and in step (1), the heating rate is 5-15 °C / min.
4. The core-shell carbon-supported PtSn4 / Pt nanoparticle catalyst according to claim 1, characterized in that: In step (2), the concentration of Pt in the Pt precursor solution (Pt-OAm) is 0.005-0.02 mmol / ml, and the drop rate of the Pt precursor solution is 0.1-0.3 ml / min.
5. The core-shell carbon-supported PtSn4 / Pt nanoparticle catalyst according to claim 1, characterized in that: In step (2), the volume ratio of oleylamine (OAm) and 1-octadecene (ODE) solution is 1:(1-3), the volume ratio of the molar amount of PtSn4 nanoparticles to oleylamine is (0.02-0.06):(2-8), unit, mol / L, and the volume ratio of Pt precursor solution (Pt-OAm) to oleylamine is (1-4):
1.
6. The core-shell carbon-supported PtSn4 / Pt nanoparticle catalyst according to claim 1, characterized in that: In step (2), the temperature is raised to 8-12°C min in an Ar atmosphere. -1 The heating rate is increased to 170-200°C and maintained for 4-8 min.
7. The core-shell carbon-supported PtSn4 / Pt nanoparticle catalyst according to claim 1, characterized in that: In step (3), the concentration of carbon black in the carbon black dispersion is 3-10 mg / ml, and the PtSn4 / Pt nanoparticles are dispersed in n-hexane, and the concentration after dispersion is 0.005-0.02 mmol / ml.
8. The core-shell carbon-supported PtSn4 / Pt nanoparticle catalyst according to claim 1, characterized in that: In step (3), the volume ratio of the carbon black dispersion to the PtSn4 / Pt nanoparticle dispersion is (1-2): (1-2).
9. Use of the core-shell carbon-supported PtSn4 / Pt nanoparticle catalyst according to claim 1 as a catalyst in electrocatalytic ethanol oxidation; The specific application methods are as follows: At room temperature, 2 mg of catalyst sample was dispersed in a mixed solution of 300 ul deionized water and 300 ul isopropanol, 100 ul of Nafion solution with a mass concentration of 0.5‰ was added, and the mixture was mixed evenly by ultrasonication for 30 minutes to obtain a catalyst slurry. Then 10 ul of the slurry was dropped onto the surface of a glassy carbon electrode with a diameter of 5 mm. After the slurry was dry, it was used as a working electrode.
Citation Information
Patent Citations
A direct ethanol fuel cell anode catalyst and preparation method thereof
CN106299396B
Preparation method of platinum-ruthenium doped rare earth element ternary alloy nano-porous catalyst for efficiently catalyzing oxidation of methanol and ethanol
CN114784296A
Propane dehydrogenation Ptx-Sny binary alloy nano-catalyst and preparation method thereof
CN107649125A
Core-shell nano-particle supported catalyzer, manufacturing method therefor, and fuel cell using the catalyzer
JP2013215697A